Seroprevalence of antibodies to hepatitis E virus in the normal blood donor population and two aboriginal communities in Malaysia - Seow, Heng-Fong; Bali Mahomed, Nizam Malik; Mak, Joon-Wah; Riddell, Michaela A.; Li, Fan; Anderson, David A. (Wiley, 1999)
The prevalence of antibodies to hepatitis E virus (HEV) has been examined in many countries, but such studies have generally been limited to majority populations such as those represented in healthy blood donors or cross sections of urban populations. Due to its major route of enteric transmission, large differences in HEV prevalence might be expected between populations in the same country but with different living conditions. Using an ELISA based on GST-ORF2.1 antigen, the prevalence of IgG-class antibodies to HEV was examined in three distinct populations in Malaysia: the normal (urban) blood donor population and two aboriginal communities located at Betau, Pahang and Parit Tanjung, Perak. IgG anti-HEV was detected in 45 (44%) of 102 samples from Betau and 15 (50%) of 30 samples from Parit Tanjung, compared to only 2 (2%) of 100 normal blood donors. The distribution of sample ELISA reactivities was also consistent with ongoing sporadic infection in the aboriginal communities, while there was no significant relationship between HEV exposure and age, sex, or malaria infection. The high prevalence of antibodies to HEV in the two aboriginal communities indicates that this group of people are at high risk of exposure to HEV compared to the general blood donors, and the results suggest that studies of HEV seroprevalence within countries must take into account the possibility of widely varying infection rates between populations with marked differences in living conditions.